Review of the genus Sorolopha Lower (Lepidoptera: Tortricidae, Olethreutinae) from Mainland China, with descriptions of two new species - Yu, Haili; Li, Houhun (Zootaxa, 2009)
The genus Sorolopha Lower from the Chinese Mainland is reviewed. Seventeen species are recognized, including two new species, S. dactyloidea sp. n. and S. identaeolochloca sp. n., and five species previously unrecorded from China, S. asphaeropa Diakonoff, 1973, S. ferruginosa Kawabe, 1989, S. karsholti Kawabe, 1989, S. liochlora (Meyrick, 1914), and S. stygiaula (Meyrick, 1933). Also, the female of S. ferruginosa is reported for the first time with a brief description and illustration. Sorolopha longurus Liu & Bai, 1982 (syn. n.) and S. micheliacola Liu, 2001 (syn. n.) are proposed as new synonyms of S. camarotis (Meyrick, 1936), and S. chlorotica Liu & Bai, 1985 (syn. n.) as a new synonym of S. rubescens Diakonoff, 1973. Photographs of adults and genitalia of the new species are provided. A key to the species from the Chinese Mainland is given based on the male genitalia.